The role of job satisfaction in the relationship between sense of calling and teacher performance - Muhammad Shohib (Jurnal Psikologi Tabularasa, 2025)
Teacher performance is a key determinant in enhancing the quality of education, as it significantly influences student achievement and overall school effectiveness. However, previous studies have highlighted consistently low levels of teacher performance across various educational levels. This study investigates the mediating role of job satisfaction in the relationship between sense of calling and teacher performance. Using a quantitative correlational design, the study involved 321 teachers in Lamongan who were over 25 years old and had at least two years of teaching experience, selected through purposive sampling. The instruments used were the Job Performance of Teacher Scale, the Teacher Job Satisfaction Scale, and the Sense of Calling Scale. Data were analyzed using Hayes’ mediation analysis method in SPSS. Results indicate that job satisfaction significantly mediates the relationship between sense of calling and teacher performance (LLCI: 0.0881; ULCI: 0.3341; p <.05). These findings suggest that enhancing teachers’ sense of calling alone is not sufficient schools must also foster job satisfaction through healthy work environments, strong professional values, and effective communication with key stakeholders to optimize teacher performance.